ChemInform Abstract: Stereospecific Allyl—Aryl Coupling Catalyzed by in situ Generated Palladium Nanoparticles in Water under Ambient Conditions. Issue 30 (4th July 2013) - Zhao, Jingming; Ye, Jiang; Zhang, Yong Jian
Abstract The cross‐coupling of secondary allylic carbonates (I) and (IV) with arylboronic acids catalyzed by in situ generated Pd‐nanoparticles without any ligands and additional stabilizers is described.